TINGKAT KEKERASAN PERMUKAAN RESIN KOMPOSIT AKIBAT MASA KEDALUWARSA MATERIAL - Yuvika Intan Ristian Putri; Muhammad Dian Firdausy; Niluh Ringga Woroprobosari (Odonto : Dental Journal, 2018)
Background: Aplication of composites resin in relatively small amount as a restorative material often causing the material reaches its expiry date before all of the material can be used. Composites resin that have passed the expiry date would aﬀect charateristic of the material. The aim of this study was to investigate surface hardness diﬀerence of composite resins based on material expiration date.Methods: This research was an experimental laboratory using post test only with control group design. Samples for this research were 27 divided into 3 groups based on its expiration date (2016, 2018 and 2019). The surface hardness was measured by Shore D Hardness. The result of this research were tested with One Way Anova and Post Hoc test LSD.Result: The lowest surface hardness result was measured on group 1 (81.02SHD) and the highest was group 3 (94.72 SHD). The result of One Way Anova test showed that there was signifcant diﬀerences in all groups (p<0.05). Post Hoc LSD test showed diﬀerence signifcantly between each groups.Conclusion: It can be concluded that there was signifcant diﬀerence of composite resins surface hardness based on material’s expiration date